Efficiency of protein extraction from palm kernel cake via different chemical extraction methods. Issue 1 (November 2020) - Chaipet, Namfon; Raita, Marisa; Siriwatwechakul, Wanwipa; Champreda, Verawat
Abstract: Protein isolation from defatted palm kernel cake (DPKC) was investigated under 3 conditions, including different chemical reagents (alkaline, saline, acidic), concentrations in the range of 0.01-0.3M and reaction time (0.5-4 h). The reaction contained 1 g biomass in 50 mL of solutions, with mixing speed 250 rpm, and the extraction occurred at 35°C for 2 hrs. Extractable protein of 35.06%, 12.40% and 4.34% based on available protein in the raw material were obtained in aqueous of 0.25M NaOH, 0.01M NaCl and 0.1M HCl. Afterward, DPKC was isolated with 0.25M NaOH for 0.5, 1, 2, 3 and 4 hrs, achieving the protein concentration of 24.16%, 28.99%, 32.72%, 34.39%, and 34.84%, respectively. The protein isolation process resulted in 48.32-60.57 %w/w and 7.27-34.60 %w/w removals of protein and ash, according to analysis of the solid residues. The oil extraction process mostly effected the composition of lignin, which can remove lignin up to 54.71% (w/w).